Analisis Faktor Yang Berpengaruh Terhadap Kepatuhan Pengunjung Warkop Pada Protokol Kesehatan Covid-19 - Abdul Latif; Muhammad Syafar; Andi Yusuf; A.Syamsinar Asmi (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: coffee shops have become community icons in big cities and developing cities to interact in the form of meetings that discuss serious things or those who are just joking and spending free time, but this becomes very dangerous when done during the Covid-19 pandemic. because it can be a medium of transmission of the disease. Objective: To determine the factors that affect the compliance of warkop visitors to the Covid-19 health protocol. Methods: The type of research used is observational (quantitative) with a Cross-Sectional Study approach. Results; shows that age = 0,556>0,05, education =0,02<0,05, knowledge =0,001<0,05, attitude =0,461>0,05. Information messages from the Covid-19 Task Force =0.032<0.05. Conclusion; Increased knowledge about the dangers of Covid-19 must be further encouraged by the Covid-19 Task Force and other parties so that people continue to apply health protocols wherever they are, especially in public places such as warkop.